Pengaruh Model Pembelajaran CTL (Contextual Teaching And Learning) Terhadap Keterampila Berpikir Kritis Peserta Didik Pada Mata Pelajaran Ekonomi: The Effect Of Contextual Teaching And Learning (CTL) Model On Students Critical Thinking Skills In Economics Class - Kartika, Ika; Sadiah, Ati; Sartika, Sri Hardianti (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) model on students' critical thinking skills in the subject of Economics. The research method employed a quasi-experimental design with a Nonequivalent Control Group Design, involving two eleventh-grade (XI) classes at SMAN 9 Garut as the research sample. The instrument used was a critical thinking skills essay test based on Ennis's indicators. The results indicated an improvement in critical thinking skills in both classes; however, the experimental class showed a more significant improvement compared to the control class. The average posttest score of the experimental class was 74.35, which was higher than the control class at 64.53, with N-Gain values of 0.36 (medium category) and 0.17 (low category), respectively. The independent sample t-test yielded a Sig. value of 0.000 < 0.05, indicating a significant difference between the two classes after the treatment. Thus, it can be concluded that CTL has a significant influence and is effective in improving students' critical thinking skills as it provides meaningful learning experiences by connecting the material with real-life contexts.